Correlation Between Low Platelet-to-Lymphocyte Ratio and High Mortality Rates in Adult Trauma Patients With Moderate-to-Severe Brain Injuries - Kang-Wei To; Shiun-Yuan Hsu; Chia-Ying Yu; Yu-Chin Tsai; You-Cheng Lin; Ching-Hua Hsieh (Emergency Medicine International)
Conclusion: Lower PLR is associated with greater mortality in adult patients with moderate-to-severe TBI. PLR may be a valuable measure for classifying mortality risk in this population.